La figure de Félix Éboué dans le discours de René Maran - Buata B. Malela (Études Caribéennes)
The biographical field offers material for colonial era intellectuals like René Maran to explore the political subject through the question of representation (or figuration) in his biographical discourse. This article is more interested in the modality by which Maran reinterprets and represents the biographical which becomes material for reflection on the political subject in his writings on the great colonial figures of which Félix Éboué constitutes a paradigmatic point of reference. Through this figure, Maran re-examines the relationship to historicity created by narration.